Analisis Pelayanan Tambat Kapal Terhadap Antrian di Terminal Peti Kemas Pelabuhan Tanjung Priok Dengan Pendekatan Algoritma Sequential Searching - Sholihah, Sita Aniisah; Bimarso, Wahyono; Haniyah, Nadaa (Institut Transportasi dan Logistik Trisakti, 2022)
The length of waiting time for ships at Tanjung Priok Port with an average length of service for ships at the Terminal reaches 0.50 hours for ships carrying domestic goods and 0.46 hours for ships carrying goods abroad. With the Sequential Searching approach algorithm with a manufacturing model using the Arena simulation application, the aim is to find out what simulation model can optimize mooring ships so that they can find ship waiting times in the queue using an approach to find ship sizes that can be used at the Tanjung Priok port container terminal so that ship mooring services can be optimal Based on the analysis carried out it is still not optimal for mooring services for small ships with an average of 153.61 hours, and there is still a high waiting time with an average of 52.59 hours, and after a simulation model for mooring services has been carried out there is a decrease in the average service time from 47.47 hours to 29.72 hours, which is 37.37%. The decrease in time indicates that the simulation used for tethering with 3 moorings is optimal.